Developing an Agile Management Framework For Project Risk Management - Saad, Ra'ed (2020)
Risk management becomes one of the most crucial processes in project and operation management nowadays. However, the accelerating rate of changes in project and business environment raises questions about the capability of traditional risk management processes to provide efficient performance. This paper aims to study the feasibility of using Scrum management methodology to run risk management and to evaluate the effect of utilizing agile management tools and techniques on the performance of risk management. This can be achieved through proposing a Scrum framework to run risk management application and assessing the professionals and academic perception about the proposed framework as well as the influence of using agile management tools and techniques in risk management by conducting an online survey. The survey showed a general acceptance from respondents to the proposed framework. Also, it presented a positive perception of the influence of employing agile tools and techniques in risk management processes. This paper showed theoretical support to the principle of using a Scrum framework for risk management. However, pilot projects are needed to confirm the feasibility of this proposal in real work. Also, this paper encourages further studies of the use of agile methodologies general and Scrum specifically for none software development applications.